Dinosaur eater : SuperCroc discovery - Eason, Sarah (Eason, Sarah. Fossils uncovered!, 2022)
Presents a graphic novel detailing paleontologist Paul Sereno's discovery of a huge, extinct crocodile nicknamed the SuperCroc and what it revealed about these creatures. Includes back matter on dinosaurs and paleontology, a glossary, and additional resources.